Combination of chemotherapy and Au-nanoparticle photothermy in the visible light to tackle doxorubicin resistance in cancer cells - Pedrosa, Pedro (2018)
Despite great advances in the fight against cancer, traditional chemotherapy has been hindered by the dose dependent adverse side effects that reduce the usable doses for effective therapy. This has been associated to drug resistance in tumor cells that often cause relapse and therapy failure. These drawbacks have been tackled by combining different therapeutic regiments that prevent drug resistance while decreasing the chemotherapy dose required for efficacious ablation of cancer. In fact, new metallic compounds have been in a continuous development to extend the existing chemotherapy arsenal for these combined regimens. Here, we demonstrate that combination of a metallic compound (TS265), previously characterized by our group, with photothermy circumvents cells resistant to Doxorubicin (DOX). We first engendered a colorectal carcinoma cell line (HCT116) highly resistant to DOX, whose viability was diminished after administration of TS265. Cancer cell death was potentiated by challenging these cells with 14 nm spherical gold nanoparticles followed by laser irradiation at 532 nm. The combination of TS265 with photothermy lead to 65% cell death of the DOX resistant cells without impacting healthy cells. These results support the use of combined chemotherapy and photothermy in the visible spectrum as an efficient tool for drug resistant tumors.